Kinetic modelling of acrylamide formation during the finish-frying of french fries with variable maltose content. (30th June 2019) - Balagiannis, Dimitrios P.; Mottram, Donald S.; Higley, Jeremy; Smith, Gordon; Wedzicha, Bronislaw L.; Parker, Jane K.
Highlights: The formation of acrylamide from maltose was investigated. Chemical reactions of acrylamide formation in french fries were modelled kinetically. The model accounted for heat and moisture transfer during typical frying conditions. Maltose contributed <10% to total acrylamide formation. The contribution from Maillard reaction vs. sugar-asparagine conjugates is discussed. Abstract: In light of a recent update in EU regulations governing levels of acrylamide in foodstuffs, further understanding of the role of different precursors is fundamental to extending mitigation strategies into a wider product range. Kinetic modelling was used to investigate the role of maltose in the formation of acrylamide during the finish-frying of french fries. The maltose concentration of raw white potato strips was systematically increased from 0 to 1.4% to observe the effect of this reducing disaccharide on acrylamide formation. A mathematical model, incorporating glucose, fructose and maltose and based on known Maillard reaction pathways, was developed which showed that acrylamide formation from maltose only contributed <10% to the total acrylamide. An additional kinetic model allowed for the formation of acrylamide directly from sugar-asparagine glycoconjugates. This model suggested that under these conditions, it is unlikely that acrylamide is formed directly from the maltose-asparagine conjugate.